AN ANALYSIS OF STUDENTS’ SKILL IN READING COMPREHENSION NARRATIVE TEXT THROUGH POWER POINT AT ELEVENTH GRADE OF SMKN 6 PADANG - Diwa Rhaudhatul Firdaus; Yessy Marzona; Sherly Franchisca (Ekasakti Educational Scientific Journal, 2024)
The objective of the research to find out the student’s skill in reading comprehension of narrative text, the student problem in reading comprehension narrative text, and the adventages of narrative text through power point. This research was conducted at SMKN 6 Padang. The academic year 2020/2021. This research used the descriptive research. The population in this research was 55 students second year of SMKN 6 Padang, namely second busana one and second busana two. In taking the sample, the researcher used cluster random sampling technique and second busana one was selected as a sample with a total of 25 students. The instrument for collecting data in this research used is reading test. This study shows that the results of the reading skills test in the average part of reading ability to determine tittle in reading narrative texts using powerpoint media are 14.52 and can be categorized as standard scores with an achievement percentage of 52% of students. In determining the main idea of a sentence in reading narrative text using powerpoint media has an average of 23.1 and can be categorized as a high score with a percentage of 52% of students. In determining the meaning of a sentence in reading narrative text using powerpoint media has an average of 17.18 and can be categorized as a standard value with a percentage of 36% of students. The final mean score of all 3 components of reading in English is 54.7 and is categorized as C or Enough. Based on the explanation above, the researcher can conclude that the students' ability to read narrative texts in English using power point media is at the moderate.